27. Sural and tibial nerve SEPs are mediated by the same spinal pathway. Issue 12 (December 2017) - Insola, A.; Mazzone, P.; Valeriani, M.
Abstract : Scalp somatosensory evoked potentials (SEPs) are later in latency after sural than after tibial nerve stimulation. This led to hypothesize that different spinal pathways could be involved in the scalp SEP generation (Rossini et al., 1986). Our aim was to investigate the SEP latencies at different subcortical sites after sural and tibial nerve stimulation. We studied 7 patients. Four patients with Parkinson's disease (PD) were implanted with intracerebral electrodes for DBS: one in the thalamus bilaterally (Vim nucleus), and 3 in the Pedunculopontine nucleus (PPTg). The remaining 3 patients were implanted with cervical epidural electrodes for intractable pain. SEPs were recorded from the scalp and the deep recording electrodes after both tibial and sural nerve stimulation. In all our patients, the scalp SEP latencies were later after sural than after tibial nerve stimulation. On the contrary, SEPs recorded at all subcortical sites showed similar latencies for both sural and tibial nerve stimulation. In conclusion, sural and tibial nerve scalp SEPs are mediated by the same spinal pathway. The difference in latency observed between the scalp SEPs after sural and tibial nerve stimulation is probably due to the orientation of the dipolar sources generating these components.